Genially program as methodological strategy to improve the pronunciation of /¿/ and /ð/ sounds in efl senior students at Arrayanes high school in Ibarra during the academic year 2020-2021 - Congo Cervantes, Marlen Mishell (2022)
To determine the Genially Program as a methodological strategy for improving the pronunciation of /θ/ and /ð/ sounds in EFL senior students at Arrayanes high school in Ibarra during the academic year 2020-2021.